Materials, design and manufacturing for lightweight vehicles - Mallick, P. K., 1946- (Woodhead Publishing in materials., 2010)
"Research into the manufacture of lightweight automobiles is driven by the need to reduce fuel consumption to preserve dwindling hydrocarbon resources without compromising other attributes such as safety, performance, recyclability and cost. This book helps engineers to not only learn about the materials being considered for lightweight automobiles, but also to compare their characteristics and properties. It discusses materials for lightweight automotive structures and reviews manufacturing and design of lightweight automotive structures. With its distinguished editor and renowned team of contributors, this book will aid the design and material selection for motor vehicle bodies and components."--Publisher's description.